Combining Ability Studies in Brinjal (Solanum melongena L.) - Sharma, Tinku Kumar; Pant, Satish Chandra; Kumar, Sandeep; Paliwal, Ajay; Bahuguna, Pankaj; Badhani, Harish Chandra (International Journal of Bio-resource and Stress Management, 2016)
Six diverse brinjal lines were crossed in a diallel fashion (excluding reciprocals) to obtain fifteen cross combinations to study combining ability for important horticultural traits. Significant differences were observed among genotypes for all the traits studied. The parent Pusa Purple Cluster emerged as good general combiner for day to first flowering, days to 50% flowering, days to first harvesting, per cent fruit set and number of fruits plant-1. Whereas, the Arka Shirish was identified as good for plant height, plant stem girth, number of primary branches plant-1, fruit length, fruit diameter and average fruit weight. Similarly Pant Samrat was good for number of flowers cluster-1 and yield plant-1. The highest specific combining ability effects in desirable direction were observed in cross Pusa Purple Cluster×Pant Samrat for days to first flowering, days to 50% flowering, days to first harvesting, plant height and per cent fruit set, Pusa Purple Cluster×Arka Shirish for plant stem girth, Pusa Purple Cluster×Arka Kusmakar for number of primary branches plant-1, Arka Neelkanth×Arka Kusmakar for fruit length (cm), Arka Shirish×Arka Kusmakar for fruit diameter, Arka Neelkanth×Arka Kusmakar for average fruit weight, Arka Nidhi×Arka Shirish for number of flowers cluster-1 and cross Pusa Purple Cluster×Pant Samrat for number of fruits plant-1 and yield plant-1.